Bribed into cooperation - Prebilič, Vladimir (Lex localis, 2019)
Due to the extreme heterogeneity of municipal sizes resulting in a number of small municipalities that are struggling to meet regulatory demands and standards, Slovenia should be the poster child for inter-municipal cooperation. This, coupled with the absence of a second level of local government, should make for flourishing inter-municipal cooperation. This article demonstrates how sound arguments for the establishment of inter-municipal cooperation do not always achieve favourable results - as in a vibrant and productive web of inter-municipal dialogue and cooperation. It was only after significant governmental subsidies were implemented in Slovenia that the municipalities initiated a cooperation process; however, that process only extended to subsidised tasks. The results of the empirical analyses show that a bottom-up process might take too long a time, while a local government (legal) framework may inhibit cooperation due to the fear oflosing authority over municipal tasks.
Keywords: Cooperation; Local self-government; Lokalna samouprava; majhne občine; medobčinsko sodelovanje; Municipalities; Občine; Sodelovanje; Subsidies; Subvencije